CULTURAL COOPERATION OF THE SOVIET REPUBLIC OF BUKHARA WITH TURKEY - Nuridinov Turdali Qambarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the history of the cultural relations established by the USSR with the state of Turkey is covered based on archival sources. It focuses on the students sent from Bukhara to Turkey in the early 20th century and in 1920-1924.